A Review of Anticancer Activity of Ferula Constituents and their Action Mechanism - Zare-Bidoki, Reza; Afrasiabi, Ali; Hajatmand-Targhi, Fatemeh Zahra; Rahimi, Hossein; Bagheri, Seyyed Majid (Current Pharmaceutical Design, 2025)
BackgroundCancer is a challenging and lethal illness, with the number of individuals affected on the rise, particularly in developing nations. This disease incurs significant expenses for both patients and governments annually. Conversely, even with various methods and treatments in use, the mortality rate remains elevated. Additionally, traditional therapies come with numerous side effects, and drug resistance presents another obstacle for physicians. Consequently, discovering new drugs derived from natural sources may be a method to combat cancer. Ferula plants contain different metabolites, including monoterpenes, sulfide compounds, and polyphenols that are beneficial in cancer therapy.ObjectiveThis article was assembled to gather evidence and literature concerning the anticancer properties of compounds derived from these plants.MethodologyThis review article was created by exploring the term Ferula isolated constituents and cancer, with related data gathered from electronic databases such as ISI Web of Knowledge, PubMed, and Google Scholar up until early 2024.ResultsResults revealed that quite extensive research has been done in this area, indicating that the compounds may serve as novel medications for cancer therapy.ConclusionSubsequent research should encompass animal studies or clinical trials, focusing on assessing toxicity and identifying effective doses against cancer to facilitate the application of these natural derivatives in cancer treatment.
Keywords: anticancer